Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.2307/2410904
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Genetics of Sprint Running Speed and Swimming Endurance in Laboratory House Mice (Mus domesticus)

Abstract: We tested the hypothesis that locomotor speed and endurance show a negative genetic correlation using a genetically variable laboratory strain of house mice (Hsd:ICR: Mus domesticus). A negative genetic correlation would qualify as an evolutionary "constraint," because both aspects of locomotor performance are generally expected to be under positive directional selection in wild populations. We also tested whether speed or endurance showed any genetic correlation with body mass. For all traits, residuals from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…Lizards' minimum prey catching and handling time of five samples is found in Van Damme et al (1991). Similar studies with interest in maxima of repeated samples of individuals have been done with fish (Tudorache et al 2007), and rodents (Djawdan andGarland 1988 andDohm et al 1996).…”
Section: Introductionsupporting
confidence: 55%
“…Lizards' minimum prey catching and handling time of five samples is found in Van Damme et al (1991). Similar studies with interest in maxima of repeated samples of individuals have been done with fish (Tudorache et al 2007), and rodents (Djawdan andGarland 1988 andDohm et al 1996).…”
Section: Introductionsupporting
confidence: 55%
“…Likewise, Gromko (1989) and Boake and Konigsberg (1998) reported negative heritabilities for courtship traits, although the estimates were not statistically significant. Nevertheless, Dohm et al (1996) found significant negative heritability estimates in some trials of house mouse sprint speed. For our housefly courtship traits, a model of genotype-by-environment interactions (where the environment is the mating partner; see Meffert 1995) can account for negative heritabilities.…”
Section: Discussionmentioning
confidence: 90%
“…Outbred, genetically variable Hsd:ICR mice (Hauschka and Mirand 1973;Dohm et al 1996;Carter et al 1999) were used to establish eight lines in 1993 (Swallow et al 1998a). In four of the lines, mice have been selected for high voluntary wheel running (measured at the age of 35 to 55 d as a total number of wheel revolutions per day); the other four have been randomly bred.…”
Section: Animalsmentioning
confidence: 99%
“…We have taken this approach with laboratory house mice (Mus domesticus) as a model system. Beginning from a base population of outbred Hsd:ICR mice (Hauschka and Mirand 1973;Dohm et al 1996), we have selected for increased levels of voluntary activity on running wheels (Swallow et al 1998a) and tested for correlated responses in various morphological and physiological traits (Swallow et al 1998b). …”
Section: Introductionmentioning
confidence: 99%